Gut morphology of diploid and triploid Atlantic salmon (Salmo salar L.) - Peruzzi, Stefano; Hagen, Ørjan; Jobling, Malcolm (Aquaculture International, 2014)
Triploid fish may differ from diploids in a number of morphological and physiological characteristics. The present study was undertaken to examine the effects of ploidy on the gut morphology of Atlantic salmon post-smolts (Salmo salar L.). For this purpose, we compared the intestinal length (relative gut length, RGL), pyloric caeca number and mass of commercially produced diploid and triploid siblings. The mean body weights of diploid and triploid salmon (n = 30 fish/ploidy) were 135 ± 1 and 132 ± 1 g, respectively. Diploid fish had significantly higher RGL (0.47 ± 0.05 vs. 0.40 ± 0.04), pyloric caeca number (56 ± 4 vs. 45 ± 3) and mass (6.41 ± 0.61 vs. 4.80 ± 0.59 g) than triploids. Morphological differences in the guts of diploids and triploids could influence digestive efficiency and play a role in determining subsequent growth or welfare of the fish.